Preoperative paroxysmal atrial fibrillation predicts high cardiovascular mortality in patients undergoing surgical aortic valve replacement with a bioprosthesis: CAREAVR study - Maunu Nissinen; Joonas Lehto; Fausto Biancari; Tuomo Nieminen; Markus Malmberg; Fredrik Yannopoulos; Samuli Salmi; Juhani K. E. Airaksinen; Tuomas Kiviniemi; Juha E. K. Hartikainen (WILEY, 2022)
Background Preoperative permanent atrial fibrillation (AF) is associated with impaired outcome after surgical aortic valve replacement (SAVR). The impact of preoperative paroxysmal AF, however, has remained elusive.Purpose We assessed the impact of preoperative paroxysmal AF on outcome in patients undergoing SAVR with bioprosthesis.
Methods A total of 666 patients undergoing isolated AVR with a bioprosthesis were included. Survival data was obtained from the national registry Statistics Finland. Patients were divided into three groups according to the preoperative rhythm: sinus rhythm (n = 502), paroxysmal AF (n = 90), and permanent AF (n = 74).
Results Patients in the sinus rhythm and paroxysmal AF groups did not differ with respect to age (P = .484), gender (P = .402) or CHA(2)DS(2)-VASc score (P = .333). At 12-month follow-up, AF was present in 6.2% of sinus rhythm patients and in 42.4% of paroxysmal AF patients (P < .001). During follow-up, incidence of fatal strokes in the paroxysmal AF group was higher compared to sinus rhythm group (1.9 vs 0.4 per 100 patient-years, HR 4.4 95% Cl 1.8-11.0, P = .001). Cardiovascular mortality was higher in the paroxysmal AF group than in the sinus rhythm group (5.0 vs 3.0 per 100 patient-years, HR 1.70 95% CI 1.05-2.76, P = .03) and equal to patients in the permanent AF (5.0 per 100 patient-years).
Conclusion Patients undergoing SAVR with bioprosthesis and history of paroxysmal AF had higher risk of developing permanent AF, cardiovascular mortality and incidence of fatal strokes compared to patients with preoperative sinus rhythm. Life-long anticoagulation should be considered in patients with a history of preoperative paroxysmal AF.